Effect of Transcutaneous Vagus Nerve Stimulation at Auricular Concha for Insomnia: A Randomized Clinical Trial - Jiao, Yue (Evid Based Complement Alternat Med, 2020)
Insomnia inflicts mental burden and decreases physical productivity and affects life quality. Transcutaneous vagus nerve stimulation (ta-VNS) may be an effective treatment option for insomnia. This study aims to evaluate the effect and safety of ta-VNS and compare it with transcutaneous nonvagus nerve stimulation (tn-VNS). A multicenter, randomized, clinical trial was conducted at 3 hospitals in China enrolling 72 insomnia participants from May 2016 to June 2017. Participants were randomly assigned (1 : 1) to receive 40 sessions of ta-VNS or tn-VNS treatment. 63 participants completed the trial. ta-VNS treatment significantly decreased the Pittsburgh Sleep Quality Index score, Epworth Sleepiness Scale score, Flinders Fatigue Scale score, Hamilton Depression Scale score, and Hamilton Anxiety Scale score over 4 weeks compared with those of the baseline. Moreover, it also significantly increased the 36-item Short-Form Health Survey Questionnaire scores compared with that of the baseline. However, it did not show significant differences compared with tn-VNS in changes of primary and secondary outcomes. The incidence of adverse events was low. ta-VNS significantly relieved insomnia over 4 weeks. Moreover, it also alleviated fatigue and improved participants' quality of life as well as other concomitant symptoms such as depression and anxiety. This trial is registered at Chinese Clinical Trial Registry (http://www.chictr.org.cn) with the registration number: ChiCTR-TRC-13003519.